Do Time, Heterochromatin, NORs, or Chromosomal Rearrangements Correlate with Distribution of Interstitial Telomeric Repeats in Sigmodon (Cotton Rats)? - Vicki J., Swier; Faisal Ali, Anwarali Khan; Robert J., Baker (The American Genetic Assosiation, 2012)
We studied the chromosomal distribution of telomere repeats (TTAGGG)n in 8 species of Sigmodon (cotton rats) using chromosome paints fluorescent in situ hybridization (FISH) from Sigmodon hispidus. In 2 species with the proposed primitive karyotype for the genus, telomere repeats were restricted to telomeric sites. But in the other 6 species that include 3 with proposed primitive karyotypes and 3 with highly rearranged karyotypes, telomere repeats were found on both telomeric sites and within interstitial telomeric sites (ITSs). To explain the distribution of ITS in Sigmodon, we gather data from C-bands, silver nitrate staining, G-bands, and chromosomal paint data from previous published studies. We did find some correlation with ITS and heterochromatin, euchromatic chromosomal rearrangements, and nucleolar organizing regions. No one type of chromosomal structure explains all ITS in Sigmodon. Multiple explanations and mechanisms for movement of intragenomic sequences are required to explain ITS in this genus. We rejected the hypothesis that age of a lineage correlates with the presence of ITS using divergence time estimate analyses. This multigene phylogeny places species with ITS (S.arizonae, S. fulviventer, S. hispidus, S. mascotensis, S. ochrognathus, and S. toltecus) in the clade with a species without ITS (S. hirsutus). Lineages with ITS (S. arizonae and S. mascotensis) arose independently from a lineage absent of ITS (S. hirsutus) around 0.67 to 0.83 Ma. The rearranged karyotypes of S. mascotensis and S. arizonae appear to be an independently derived autapomorphic characters, supporting a fast rate of chromosomal changes that vary among species.